An in situ synthesis of silver nanoparticle-loaded genetically engineered polypeptide nanogels for antibacterial and wound healing applications. Issue 34 (20th August 2020) - Zhao, Dong-Hui; Yang, Jie; Yao, Ming-Hao; Li, Chao-Qing; Zhang, Bin; Zhu, Dan; Zhao, Yuan-Di; Liu, Bo
Abstract : One-step in situ synthesis of Ag nanoparticle encapsulated in polypeptide nanogels for antibacterial and wound healing. Abstract : The fact that the wounds infected by bacteria are difficult to heal is a major health issue. Herein, we synthesized silver nanoparticle-loaded polypeptide nanogels via an in situ method using UV irradiation, which is a relatively green and simple method. The size of the nanogel and silver nanoparticles could be regulated by changing the concentrations of the polypeptide and silver ions, respectively. Because the polypeptide PC10 ARGD was histidine-rich and biodegradable, the as-synthesized silver nanogels exhibited low toxicity and good biocompatibility. The in vitro antibacterial experiments showed that the silver nanogels presented excellent antibacterial activity against both Gram-negative and Gram-positive bacteria. Moreover, silver nanogels had a good effect as an antibacterial and wound healing agent in vivo . These findings provide a new strategy and theoretical basis for the synthesis and application of silver nanoparticles.